2009
DOI: 10.3168/jds.2008-1648
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lameness in cows kept in tie-stalls

Abstract: Identifying lame cows and quantifying the prevalence of lameness are important elements of cattle welfare assessment that are generally achieved by methods involving observations of each animal walking. There is no published method for assessing lameness in cows confined in tie-stalls. The objective of this study (carried out within the European Commission's Welfare Quality(R) project) was to develop a suitable method and validate it for lameness detection against a published locomotion score. A series of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 23 publications
6
79
2
1
Order By: Relevance
“…Additionally, some studies suggest that continuously tethered animals tend to have more skin injuries compared with systems with access to loafing areas, pasture and loose housed cattle (13,19). Although the proposed method for assessing the lameness in tied cows is different from the one for loose animals (8), at least severely lame may be reliably detected (22). The prevalence of lameness had wide range in the assessed farms, but not exceeding 16.2% per farm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies suggest that continuously tethered animals tend to have more skin injuries compared with systems with access to loafing areas, pasture and loose housed cattle (13,19). Although the proposed method for assessing the lameness in tied cows is different from the one for loose animals (8), at least severely lame may be reliably detected (22). The prevalence of lameness had wide range in the assessed farms, but not exceeding 16.2% per farm.…”
Section: Discussionmentioning
confidence: 99%
“…Lameness was assessed using in-stall lameness scores developed by Leach et al (2009) and validated by Gibbons et al (2014). Cows were individually video recorded using a Sony DCRSR88 camera (Sony, Tokyo, Japan) in their stalls from behind for 2.5 min.…”
Section: Animal-based Measuresmentioning
confidence: 99%
“…The method used to score the cows for lameness in the stall was Table 1 Description of lesion scores assigned to cows (Gibbons et al, 2012). Leach et al (2009) and adapted by Gibbons et al (2014), who showed this stall lameness scoring method is strongly correlated with that obtained from gait scoring. Scoring involved observing the cows in the tiestall for four behaviors.…”
Section: Lameness Scoresmentioning
confidence: 99%